Cat-eye conundrum - Tengku Azizan, Tengku Rinalfi Putra; Ahmad, Hafandi; Mohd Noor, Mohd Hezmee; Abu Hassim, Hasliza; Azmi, Mohd Azri; Abd Halim Shah, Muhammad Muzammil; Ab. Latip, Mohd Qayyum (Universiti Putra Malaysia Press, 2017)
Due to the predictability of light reflection, natural selection has chosen the eyes of some animals to be a light reflective organ. Light reflection is very useful in animals with night vision whereby the light that is reflected by the eye is used for illumination in low light conditions.